2018
DOI: 10.3171/2017.9.spine17494
|View full text |Cite
|
Sign up to set email alerts
|

Spinal ependymoma in adults: a multicenter investigation of surgical outcome and progression-free survival

Abstract: OBJECTIVESpinal ependymomas are rare glial neoplasms. Because their incidence is low, only a few larger studies have investigated this condition. There are no clear data concerning prognosis and therapy. The aim of the study was to describe the natural history, perioperative clinical course, and local tumor control of adult patients with spinal ependymomas who were surgically treated under modern treatment standards.METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 33 publications
2
36
0
5
Order By: Relevance
“…A case series of ependymoma reported that the Ki-67 labeling index appeared to be an important prognostic factor [14]. While Ki-67 labeling index values of less than 4.0 have been associated with long survival times, a predictive threshold has not been established [15].…”
Section: Discussionmentioning
confidence: 99%
“…A case series of ependymoma reported that the Ki-67 labeling index appeared to be an important prognostic factor [14]. While Ki-67 labeling index values of less than 4.0 have been associated with long survival times, a predictive threshold has not been established [15].…”
Section: Discussionmentioning
confidence: 99%
“…▪ Karzinommetastasen: 1 -3 % aller intramedullären Tumoren, schlechte Prognose, OP rein palliativ bei progredienten Defiziten ▪ Dysontogenetische Tumore (Lipome, Epidermoide, häufiger aber intradural extramedullär) ▪ Nervenscheidentumore (die absolute Mehrheit sind extramedullär) teil. Nur 60 % sind rein intramedulläre Läsionen [6]. Der eigentliche Tumor ist i. d. R. ein kleiner hypervaskularisierter Knoten (Nidus).…”
Section: Klinikunclassified
“…Während der Nachweis spezifischer Mutationen bei der Klassifikation zerebraler Gliome inzwischen eine zentrale Rolle einnimmt, bleiben diese genetischen Aspekte bei spinalen Ependymomen im Wesentlichen bislang unbekannt. Zusätzlich wird die Bestimmung von Proliferationsindex Ki67 empfohlen, da dieser ein zuverlässigerer Prognosefaktor als die aktuelle WHO-Einteilung zu sein scheint [6].…”
Section: Postoperativer Verlauf Und Prognoseunclassified
“…Die sagittale Ausdehnung des Tumors definiert die Längsausdehnung der Läsion in der sagittalen Schnittbildgebung und bestimmt die Länge der knöchernen Freilegung. Der überwiegende Anteil intraduraler, extramedullärer Raumforderungen kann über einen posterioren Zugang erreicht werden [10,11]. Hierbei stellt die Hemilaminektomie, ggf.…”
Section: Operationsplanung Und Anatomische üBerlegungenunclassified
“…Die Komplikationsrate durch eine Operation liegt zwischen 4,6 -6,3 Prozent [5]. Die häufigsten chirurgischen Komplikationen sind Nachblutung, Wundinfektion und Liquorfistel [10,11]. Bei vollständiger Resektion des Tumors ist das Rezidivrisiko gering und liegt bei 3 -7 % bei Meningeomen und 5 % bei Neurinomen [6,14,15].…”
Section: Op-assoziierte Komplikationen Und Outcomeunclassified